Enamel remineralization after extracoronal bleaching using nano-hydroxyapatite (nha) from synthesis results of blood clam (anadara granosa) shells - Noor Hikmah; Juni J. Nugroho; Nurhayaty Natsir; Christine A. Rovani; Latieif Mooduto (Journal of Dentomaxillofacial Science, 2019)
Objective: Nano-hydroxyapatite (nHA) is considered effective in stimulating the occurrence of enamel remineralization after application of bleaching materials. Nano-hydroxyapatite (nHA) can be synthesized from the shell of the blood clam (Anadara granosa) and the substances contained can be measured using X-ray diffraction (XRD).Material and Methods: The samples used in this study were 6 premolars of one upper jaw prepared by buccal and palatal crown with size of 5Ã—5Ã—2 mm (12 enamel disc), soaked in saline solution then divided into 2 treatment groups. Initial calcium percentage examinations were performed on each sample before bleaching material application. Next, bleaching material was applied to the sample according to the manufacturer's instructions and calcium level in each treatment group was re-examined. Application of CPP-ACP paste and nHA synthesis of blood clam (anadara granosa) shells was performed after bleaching with an hour application time per day for 7 consecutive days, and re-examined afterwards. The calcium percentage examination is performed using Energy Dispersive X-Ray Spectroscopy (EDS) tools. Data are collected and examined.Results: Data were collected and analyzed using independent t test. The results indicate that remineralization with nHA from synthesis results of blood clam shells increased the calcium levels of samples that had been extracoronally bleached, but statistically there was no significant difference with the value of p = 0.345 (p> 0.05)Conclusion: The nano-hydroxyapatite (nHA) application of blood clam shells (Anadara granosa) synthesis results can increase the percentage of calcium after the application of extracoronal bleaching materials.